FEM of Gas-Assisted Injection Molding Based on 3D Model - Xinchao Wang; Tie Geng; Liqun Yan; Yonggang Guo; Lih-Sheng Turng (Advances in Polymer Technology)
The gas-assisted injection molding (GAIM) process is so complicated that increasing reliance has been placed on CAE (Computer Aided Engineering) as a tool for both mold designers and process engineers. In this paper, a 3D theoretical model and numerical scheme is presented to simulate the GAIM process, in which an equal-order velocity-pressure formulation method is employed to eliminate the pressure oscillation. In addition, the whole flow field including the gas and melt regions is calculated using a uniform momentum equation with the viscosity of gas raised to a certain order of magnitude, and a 3D control volume scheme is employed to track the flow front of the melt and gas. Finally, the validity of the model has been tested through case studies and experimental verification.